Search-based software engineering : 7th International Symposium, SSBSE 2015, Bergamo, Italy, September 5-7, 2015 : proceedings /: 7th International Symposium, SSBSE 2015, Bergamo, Italy, September 5-7, 2015 : proceedings. ([2015]) - Unknown
No abstract available